PENGARUH KUALITAS PRODUK, PELAYANAN DAN PROMOSI ONLINE TERHADAP PEMBELIAN CATERING SALAMAH AQIQAH CV. MITRA TANI FARM - Adistie Erina Salsadila; Achmad Firman; Anita Fitriani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Research on "The Effect of Product Quality, Service and Online Promotion on Purchase Decisions for Catering Salamah Aqiqah CV. Mitra Tani Farm" has been carried out in May-April 2022 at Salamah Aqiqah CV. Mitra Tani Farm, Tegal Waru Village, Ciampea District, Bogor Regency. The purposes of this study were to determine the effect of product quality, service, online promotion and two additional variables such as price and location either simultaneously or partially on the decision to purchase aqiqah catering. The research method used was a survey of 37 respondents using a questionnaire (google form) as a tool. The data obtained were analyzed using ordinal regression analysis. The results showed that  all variables had simultaneous influence on the decision to purchase aqiqah catering with a model accuracy of 98.9%. Meanwhile, only the product quality and location variables had partial effect on the decision to purchase aqiqah catering.